Feasibility and safety of using Soehendra stent retriever as a new technique for biliary access in endoscopic ultrasoundguided biliary drainage - Varayu Prachayakul (2018)
© The Author(s) 2015. Published by Baishideng Publishing Group Inc. All rights reserved. AIM: To assess the feasibility and safety of the use of soehendra stent retriever as a new technique for biliary access in endoscopic ultrasound-guided biliary drainage. METHODS: The medical records and endoscopic reports of the patients who underwent endoscopic ultrasound-guided biliary drainage (EUS-BD) owing to failed endoscopic retrograde cholangiopancreatography in our institute between June 2011 and January 2014 were collected and reviewed. All the procedures were performed in the endoscopic suite under intravenous sedation with propofol and full anaesthetic monitoring. Then we used the Soehendra stent retriever as new equipment for neo-tract creation and dilation when performing EUS-BD procedures. The patients were observed in the recovery room for 1-2 h and transferred to the regular ward, patients' clinical data were reviewed and analysed, clinical outcomes were defined by using several different criteria. Data were analysed by using SPSS 13 and presented as percentages, means, and medians. RESULTS: A total of 12 patients were enrolled. The most common indications for EUS-BD in this series were failed common bile duct cannulation, duodenal obstruction, failed selective intrahepatic duct cannulation, and surgical altered anatomy for 50%, 25%, 16.7%, and 8.3%, respectively. Seven patients underwent EUS-guided hepaticogastrostomy (58.3%), and 5 underwent EUS-guided choledochoduodenostomy (41.7%). The technical success rate was 100%, while the clinical success rate was 91.7%. Major and minor complications occurred in 16.6% and 33.3% of patients, respectively, but there were no procedurerelated death. CONCLUSION: Soehendra stent retriever could be used as an alternative instrument for biliary access in endoscopic ultrasound guided biliary drainage.